Elementary School Students' Responses to Open-Ended Learning Materials Integrated with Regional Culture on Fractions, as Seen From the Cognitive Level - Hs, Atika Maulidina; Wiryanto, Wiryanto; Mariana, Neni; Huda, M.Misbachul; Ananta, Maulana Paramaditya; Bambang, Bambang (Literasi Nusantara, 2026)
This study aims to gain in-depth understanding of students' responses to the use of open-ended teaching materials integrated with local wisdom. This study used a descriptive qualitative approach, taking fourth-grade students of SDN Demangan 1 Bangkalan as subjects. Data were collected through student response questionnaires, interviews, observations, and documentation. The collected data were analyzed through data reduction, data presentation, and conclusion drawing stages, with data validity checked through technical triangulation. The results showed that, in general, students gave a very positive response with an average response score of 3.44 to the use of teaching materials. Positive responses were seen in increased student interest in mathematics learning, particularly through the integration of local wisdom content, increased enthusiasm for learning, self-confidence, and student involvement in discussions. Further analysis showed variations in responses based on students' cognitive levels, but all students, whether at high, medium, or low cognitive levels, showed positive attitudes toward the use of teaching materials. Thus, open-ended teaching materials based on local wisdom have the potential to be a relevant alternative to support meaningful mathematics learning in elementary schools.